Answer: n= 32
Jakes started with 32
Step-by-step explanation:
Let n represent the initial integer.
Step 1: take the reciprocal.
Reciprocal of n = 1/n
Step 2: double the number obtained in step 1
= 2×1/n = 2/n
Step 3: take the reciprocal of the number obtained in step 2.
Reciprocal of 2/n = n/2
Since he ended up with 16
n/2 = 16
n = 2×16 = 32
Answer:
(
, 3 )
Step-by-step explanation:
Given the 2 equations
y = 9x → (1)
6x - y = - 1 → (2)
Substitute y = 9x into (2)
6x - 9x = - 1, that is
- 3x = - 1 ( divide both sides by - 3 )
x = ![\frac{1}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D)
Substitute x =
into (1) for corresponding value of y
y = 9 ×
= 3
Solution is (
, 3 )
Let
x-------> Leila 's profit
y------> Jo's profit
we know that
----------> equation ![1](https://tex.z-dn.net/?f=%201%20)
For ![y=\$60](https://tex.z-dn.net/?f=%20y%3D%5C%2460)
<u>Find the value of x</u>
Substitute the value of y in the equation ![1](https://tex.z-dn.net/?f=%201%20)
![\frac{x}{60} =\frac{3}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bx%7D%7B60%7D%20%3D%5Cfrac%7B3%7D%7B4%7D)
![x=60*\frac{3}{4}](https://tex.z-dn.net/?f=x%3D60%2A%5Cfrac%7B3%7D%7B4%7D)
![x=\$45](https://tex.z-dn.net/?f=%20x%3D%5C%2445)
therefore
<u>the answer is</u>
Leila make
in profit
Answer:
Simplifying the expression:
we get ![\mathbf{42x-100y-360}](https://tex.z-dn.net/?f=%5Cmathbf%7B42x-100y-360%7D)
Step-by-step explanation:
We need to simplify the expression: ![2(\frac{3}{5}x+\frac{2}{3}y-\frac{1}{4}x-1\frac{1}{2}y +3)](https://tex.z-dn.net/?f=2%28%5Cfrac%7B3%7D%7B5%7Dx%2B%5Cfrac%7B2%7D%7B3%7Dy-%5Cfrac%7B1%7D%7B4%7Dx-1%5Cfrac%7B1%7D%7B2%7Dy%20%2B3%29)
First we will solve terms inside the bracket
![2(\frac{3}{5}x+\frac{2}{3}y-\frac{1}{4}x-1\frac{1}{2}y +3)](https://tex.z-dn.net/?f=2%28%5Cfrac%7B3%7D%7B5%7Dx%2B%5Cfrac%7B2%7D%7B3%7Dy-%5Cfrac%7B1%7D%7B4%7Dx-1%5Cfrac%7B1%7D%7B2%7Dy%20%2B3%29)
Converting mixed fraction
into improper fraction, we get: ![\frac{3}{2}y](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B2%7Dy)
Replacing the term:
![2(\frac{3}{5}x+\frac{2}{3}y-\frac{1}{4}x-\frac{3}{2}y +3)](https://tex.z-dn.net/?f=2%28%5Cfrac%7B3%7D%7B5%7Dx%2B%5Cfrac%7B2%7D%7B3%7Dy-%5Cfrac%7B1%7D%7B4%7Dx-%5Cfrac%7B3%7D%7B2%7Dy%20%2B3%29)
Now, taking LCM of: 5,3,4,2 we get 60
Now multiply 60 with each term inside the bracket
![2(\frac{3}{5}x\times60+\frac{2}{3}y\times60-\frac{1}{4}x\times60-\frac{3}{2}y\times60 +3\times60)\\2(3x\times12+2y\times20-1x\times15-3x\times30-3\times60)\\2(36x+40y-15x-90y-180)](https://tex.z-dn.net/?f=2%28%5Cfrac%7B3%7D%7B5%7Dx%5Ctimes60%2B%5Cfrac%7B2%7D%7B3%7Dy%5Ctimes60-%5Cfrac%7B1%7D%7B4%7Dx%5Ctimes60-%5Cfrac%7B3%7D%7B2%7Dy%5Ctimes60%20%2B3%5Ctimes60%29%5C%5C2%283x%5Ctimes12%2B2y%5Ctimes20-1x%5Ctimes15-3x%5Ctimes30-3%5Ctimes60%29%5C%5C2%2836x%2B40y-15x-90y-180%29)
Now, combine like terms
![2(36x-15x-90y+40y-180)\\2(21x-50y-180)](https://tex.z-dn.net/?f=2%2836x-15x-90y%2B40y-180%29%5C%5C2%2821x-50y-180%29)
Now, multiply all terms with 2
![42x-100y-360](https://tex.z-dn.net/?f=42x-100y-360)
So, Simplifying the expression:
we get ![\mathbf{42x-100y-360}](https://tex.z-dn.net/?f=%5Cmathbf%7B42x-100y-360%7D)
Hi , 3/4 times 28 equals to 84/4
28 is equivalent to 28/1
we just multiply straight across
28 x 3 equals to 84
4 x 1 equals to 4
<span />